Identification of the etiological agent of equine piroplasmosis in Western and Eastern Siberia - V. A. Rar; V. A. Marchenko; E. A. Efremova; O. V. Suntsova; O. V. Lisak; A. Y. Tikunov; I. V. Meltsov; N. V. Tikunova (Вавиловский журнал генетики и селекции)
Equine piroplasmosis is a natural tick-borne infection caused by hemoprotozoan parasites of the order Piroplasmida, Babesia caballi and Theileria equi. Animals that recover from piroplasmosis remain persistently infected carriers and can transmit pathogens to vector ticks. Cases of equine piroplasmosis are periodically observed in Siberia, however, no agent of equine piroplasmosis has yet been genetically characterized in Russia. The aim of this work was studying the prevalence of the infectious agents of piroplasmosis in horses from Siberia and genotyping the detected agents. Blood samples from 155 horses were examined for the presence of Babesia and Theileria DNA by nested PCR with the subsequent sequencing of positive samples. DNA of T. equi was found in blood samples from 57.9 %, 38.5 % and 65.0 % of horses from Novosibirsk province, Irkutsk province, and the Republic of Altai, respectively. T. equi DNA was found in the samples from almost all sampling sites included in this study, indicating that most of the studied sites are endemic for equine theileriosis. Surprisingly, DNA of B. caballi was not found in any of the samples examined, even though this agent had previously been detected in many regions in Russia, including Altai. The analysis of the determined 18S rRNA gene sequences demonstrated that T. equi samples belonged to two genetic groups, which differed significantly by the sequences of the variable (V4) region of the gene. All T. equi sequences from group B were identical and corresponded to T. equi sequences found in the blood of horses from China and Korea, while T. equi sequences from group A differed by 1–5 nucleotide substitutions and were identical to the sequences from the blood of horses from India and Brazil or differed from them by single mismatches. Notably, in this study the presence of etiological agent of piroplasmosis in blood samples from horses in Russia was genetically confirmed for the first time.